Effect of charge redistribution factor on stacking-fault energies of Mg-based binary alloys. (February 2016) - Wu, Y.F.; Li, S.; Ding, Z.G.; Liu, W.; Zhao, Y.H.; Zhu, Y.T.
Abstract: The energies of deformation fault (I2 ) and twin-like fault (T2 ) of thirteen binary Mg alloys were studied using density functional theory. It is shown that the faulted regions are energetically favorable for solute segregation, and the reduction of stacking-fault energy (SFE) was caused by charge redistribution. We define a charge redistribution factor, F, to quantify the solute-induced charge redistribution. An analytical model was established to calculate SFE from F. Graphical abstract: